2021
DOI: 10.1055/s-0041-1728744
|View full text |Cite
|
Sign up to set email alerts
|

BCL11A Polymorphism in Egyptian Children with β-Thalassemia: Relation to Phenotypic Heterogeneity

Abstract: Fetal hemoglobin (HbF) is a potent genetic modifier of β-thalassemia phenotype. B-cell lymphoma 11A (BCL11A) gene results in significant silencing of HbF. The aim of this study was to assess the prevalence of different BCL11A genotypes among a cohort of Egyptian children with β-thalassemia and to correlate them to HbF and clinical severity score. Eighty-two children with β-thalassemia (aged 12.95 ± 3.63 years) were recruited from the Pediatric Hematology Clinic, Ain Shams University. They were divided based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Fetal hemoglobin (HbF) is considered as a potent genetic modifier of β-Thalassemia and Sickle cell disease phenotype. 8 Patients with high HbF levels have shown to have longer life expectancy and lesser complications. 9 It has been shown that three genetic loci that carry DNA polymorphisms in BCL11A, β-globin and HBS1L-MYB genes are involved in modulation of HbF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal hemoglobin (HbF) is considered as a potent genetic modifier of β-Thalassemia and Sickle cell disease phenotype. 8 Patients with high HbF levels have shown to have longer life expectancy and lesser complications. 9 It has been shown that three genetic loci that carry DNA polymorphisms in BCL11A, β-globin and HBS1L-MYB genes are involved in modulation of HbF levels.…”
Section: Discussionmentioning
confidence: 99%